The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1747-597x-6-27
|View full text |Cite
|
Sign up to set email alerts
|

Is there a danger for myopia in anti-doping education? Comparative analysis of substance use and misuse in Olympic racket sports calls for a broader approach

Abstract: BackgroundRacket sports are typically not associated with doping. Despite the common characteristics of being non-contact and mostly individual, racket sports differ in their physiological demands, which might be reflected in substance use and misuse (SUM). The aim of this study was to investigate SUM among Slovenian Olympic racket sport players in the context of educational, sociodemographic and sport-specific factors.MethodsElite athletes (N = 187; mean age = 22 ± 2.3; 64% male) representing one of the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 56 publications
3
40
0
3
Order By: Relevance
“…Optimal nutrition may reduce fatigue and injuries, promote recovery from injuries, optimize the body's energy stores and consequently positively influence one's health status [18][19][20]. Due to the training duties and performances, dancers are frequently unable to eat adequately and therefore the relatively high prevalence of the NS in our participants (almost 2/3 of the dancers consume the NS) is not surprising and is consistent with previous reports [3,5].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Optimal nutrition may reduce fatigue and injuries, promote recovery from injuries, optimize the body's energy stores and consequently positively influence one's health status [18][19][20]. Due to the training duties and performances, dancers are frequently unable to eat adequately and therefore the relatively high prevalence of the NS in our participants (almost 2/3 of the dancers consume the NS) is not surprising and is consistent with previous reports [3,5].…”
Section: Discussionsupporting
confidence: 78%
“…Many controversies remain about the possible efficacy and necessity of this behavior [18]. Yet it is also confirmed that the NS provide potentially important nutrients for those individuals who are involved in physically demanding activities [19].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we studied a relatively small sample, but we included a significant proportion of the SAF members in Croatia and selected them randomly. Consequently, the percentage of respondents was almost maximal, which is known to be a more important factor of plausibility than the number of subjects per se [24]. Apart from the fact that a low response rate can give rise to sampling bias, the fact that we had almost a maximal response rate gave us right to conclude that the subjects felt comfortable when the questionnaire was administered.…”
Section: Study Limitationsmentioning
confidence: 92%
“…The evaluated variables included those collected by the Questionnaire of Substance Use (QSU). QSU is a tool that had been previously used and validated to determine the SUM patterns among different physically active professionals and athletes [24][25][26][27]. QSU collects socio-demographic data and comprises profession-related questions (in this case, military-specific questions) and questions on SUM.…”
Section: Introductionmentioning
confidence: 99%
“…This topic is beyond the scope of this article and has been discussed elsewhere. 21,22 However, because the course of cLBP may be protracted, 23 patients may require treatment over years or decades. Therefore, it is critical that the risks and benefits of pharmacotherapies are closely evaluated to ensure that short-and long-term treatments are optimized for each patient.…”
Section: Introductionmentioning
confidence: 99%